Parents and high school students’ social interaction - Saputra, Muhammad Oktarico; Darmayanti, Kusumasari Kartika Hima; Meyrinda, Jesyia; Zaharuddin, Zaharuddin; Afifah, Sarah; Despiana, Dwi; Fadhli, Muhammad; Winata, Efan Yudha (Journal of Education and Learning (EduLearn), 2025)
Parenting style is an essential factor for social anxiety, but research from different countries showed inconsistent empirical evidence. Therefore, this research examines the influence of parenting style (parental demandingness and responsiveness) on social anxiety among high school students in Indonesia. Four hundred high school students in Palembang City, Indonesia, were involved, with girls (n=244, 61%) and boys (n=156, 39%). The results of path analysis using the Mplus 7 showed that maternal (β=-0.123; p=0.001) and paternal demandingness (β=-0.149; p=0.020) significantly negatively influence social anxiety. For the responsive parenting style, the results found that maternal (β=0.035; p=0.026) and paternal responsiveness (β=0.649; p=0.000) positively influence high school students' social anxiety. Parenting styles explain 35.3% of social anxiety variance. This finding become a reference as a program to intervene in students’ social anxiety based on demanding and responsive parenting styles.